2019
DOI: 10.3389/fnins.2019.01329
|View full text |Cite
|
Sign up to set email alerts
|

Baroreflex Sensitivity Predicts Response to Metoprolol in Children With Vasovagal Syncope: A Pilot Study

Abstract: Objective: To explore the role of baroreflex sensitivity (BRS) in the head-up tilt test (HUTT) in predicting the therapeutic response of vasovagal syncope (VVS) patients to metoprolol. Materials and Methods: Vasovagal syncope patients treated with metoprolol were enrolled in this study and were classified as responders or non-responders according to changes in their symptom scores before and after metoprolol treatment. Values of BRS in the supine position and at positive response occurrence in the HUTT were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…The protocol for the HUTT and the positive response criteria were in accordance with those previously described. [ 19 , 20 ] Three types of positive hemodynamic responses were identified according to the changes in heart rate and blood pressure: 1) a cardioinhibitory response, with an obvious reduction in heart rate and no marked decrease in blood pressure; 2) a vasoinhibitory response, with a marked decrease in blood pressure and no obvious reduction in heart rate; and 3) a mixed inhibitory response, with both an obvious blood pressure decrease and a significant heart rate reduction.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The protocol for the HUTT and the positive response criteria were in accordance with those previously described. [ 19 , 20 ] Three types of positive hemodynamic responses were identified according to the changes in heart rate and blood pressure: 1) a cardioinhibitory response, with an obvious reduction in heart rate and no marked decrease in blood pressure; 2) a vasoinhibitory response, with a marked decrease in blood pressure and no obvious reduction in heart rate; and 3) a mixed inhibitory response, with both an obvious blood pressure decrease and a significant heart rate reduction.…”
Section: Methodsmentioning
confidence: 99%
“…The therapeutic efficacy was determined to be effective when the symptom score decreased by at least 1 point, and correspondingly, these patients were considered “responders”; otherwise, they were considered “non-responders” [Figure 1 ]. [ 20 , 21 ] All follow-up tasks were completed by the same professionally trained researcher.…”
Section: Methodsmentioning
confidence: 99%
“…When CK-MB was 23.94 U/L, the sensitivity and specificity of diagnosing VVS were 71.10 and 66.70%, respectively. Tao et al [ 21 ] reported therapeutic response of baroreflex sensitivity (BRS) in predicting VVS patients to metoprolol, and compared with non-responders, patients with reaction showed a significant increase in BRS value in supine position. When BRS cut-off value was 10 ms/mmHg, the sensitivity and specificity of predicting an intervention response were 82 and 83%.…”
Section: Discussionmentioning
confidence: 99%
“… 1 The severity of the disease was assessed by the syncope symptom score based on the frequency of syncope episodes. 29 , 46 , 47 The syncope symptom score was as follows: 0, no syncope; 1, once/month; 2, two to four times/month; 3, two to seven times/week; 4, more than once per day. 29 , 30 , 46 , 47 The baseline syncope symptom score was evaluated by the average frequency of syncope episodes within 3 months before metoprolol treatment.…”
Section: Methodsmentioning
confidence: 99%
“… 29 , 46 , 47 The syncope symptom score was as follows: 0, no syncope; 1, once/month; 2, two to four times/month; 3, two to seven times/week; 4, more than once per day. 29 , 30 , 46 , 47 The baseline syncope symptom score was evaluated by the average frequency of syncope episodes within 3 months before metoprolol treatment. After 3 months of metoprolol treatment, all the patients were followed up by hospitalization, outpatient clinics or telephone, and their frequency of syncope episodes during the metoprolol treatment and the treatment compliance were collected, recorded, and checked by professional investigators.…”
Section: Methodsmentioning
confidence: 99%